2012
DOI: 10.25035/ijare.06.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Swim Instructor Beliefs About Toddler and Pre-School Swimming and Water Safety Education

Abstract: To study the teacher component of the parent-teacher-learner triad in preschool aquatics and explore compatibility of instructor messages with current drowning prevention beliefs, 133 preschool aquatics instructors were surveyed. Instructors with basic swim teacher accreditation and those with a preschool/infant instructor extension ("Extension") were compared. More Extension instructors selected "safety" as an important outcome (χ 2 = 7.907, df = 3, p = 0.048). Both instructor groups considered parental educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
0
4
0
2
Order By: Relevance
“…Fewer supported CPR training via their health professionals (58%) or via online computer programs (48%). A recently-reported Australian study on swim school instructor beliefs on toddler water safety education suggested that almost all (97%) of the 133 respondents considered themselves capable of performing child CPR, although this study did not explore instructors capacity to teach CPR or the recency of their training (Blitvich, Moran, Petrass, McElroy, & Stanley, 2012). In light of this background and perceived needs, it was the purpose of the current study to devise and evaluate a pilot parent education program aimed at enhancing the CPR knowledge and confidence of parents while their young children were enrolled in lessons in commercial swim schools.…”
mentioning
confidence: 92%
“…Fewer supported CPR training via their health professionals (58%) or via online computer programs (48%). A recently-reported Australian study on swim school instructor beliefs on toddler water safety education suggested that almost all (97%) of the 133 respondents considered themselves capable of performing child CPR, although this study did not explore instructors capacity to teach CPR or the recency of their training (Blitvich, Moran, Petrass, McElroy, & Stanley, 2012). In light of this background and perceived needs, it was the purpose of the current study to devise and evaluate a pilot parent education program aimed at enhancing the CPR knowledge and confidence of parents while their young children were enrolled in lessons in commercial swim schools.…”
mentioning
confidence: 92%
“…Ceturtajā zināšanu komponentē iekļauts saturs par drošību un drošināšanu uz ūdens, veicot zīdaiņu peldināšanu (Brenner, Gitanjali, & Gordon, 2003;Blitvich et al, 2012):…”
Section: Review Of Literature and Discussionunclassified
“…In the United States and elsewhere, researchers have focused on exploring aquatic instructors' attitudes and beliefs in teaching individuals with disabilities (Blitvich, Moran, Petrass, McElroy, & Stanley, 2012;Conatser, 2007bConatser, , 2008Conatser, Block, & Gansneder, 2002;Sato & Hodge, 2012). For instance, Conatser (2008) surveyed aquatic instructors from seven countries (New Zealand, Australia, Cayman Islands, Germany, Canada, Mexico, and Argentina) to assess their attitudes 2 International Journal of Aquatic Research and Education, Vol.…”
Section: Ijare Vol 9 No 3 2015mentioning
confidence: 99%